REVIEW-PandemicTerm - A MULTILINGUAL CONTEXTUALIZED GLOSSARY - Mirela Costeleanu (Studii de gramatică contrastivă)
Reference: PandemicTerm - A Multilingual Contextualized Glossary, Tomescu, Ana-Marina, Ilinca, Cristina-Elena, Boncescu, Silvia, 202